PENGGUNAAN FITUR INSTAGRAM UNTUK PENINGKATAN PROFIT UMKM GARMEN MENGGUNAKAN METODE ACTION RESEARCH - Karina Nine Amalia; Tri Agustina Nugrahani; Gayatri Dwi Santika (Journal of Innovation Research and Knowledge, 2022)
Along with the development of digital technology today, social media is a platform for sharing information that is very liked by many people. Indonesia is one of the countries with the most Instagram users. This shows a high increase in Indonesian consumers towards social media so that it can increase user interest in advancing MSMEs in Indonesia. One of the MSMEs that play an important role in improving the Indonesian economy is Garment MSMEs. Garment MSMEs currently have several major problems in terms of market research, competition, creating trends, and scientific approaches to introducing fashion products in the market. Another problem for garment SMEs is product availability. An accurate response is one strategy for companies to deal with uncertainty in supply and demand. An accurate response will get a decision that can be used as a consideration for making a product. This study uses the Action Research method to analyze the impact of social media features on design and market research. The action research method used in this study is the reason that previous research still uses historical data as material for data collection in research. The steps of the action research method are diagnostic, action planning, action intervention, action evaluation, and action-reflection. The results of the study prove that the features on Instagram's social media can affect the accuracy of planning and manufacturing garment MSME products as well as increase sales